Integrated breeding approaches to enhance the nutritional quality of food legumes - Jha, Rintu; Yadav, Hemant Kumar; Raiya, Rahul; Singh, Rajesh Kumar; Jha, Uday Chand; Sathee, Lekshmy; Singh, Prashant; Thudi, Mahendar; Singh, Anshuman; Chaturvedi, Sushil Kumar; Tripathi, Shailesh (Frontiers in Plant Science, 2022)
Global food security, both in terms of quantity and quality remains as a challenge with the increasing population. In parallel, micronutrient deficiency in the human diet leads to malnutrition and several health-related problems collectively known as ‘hidden hunger’ more prominent in developing countries around the globe. Biofortification is a potential tool to fortify grain legumes with micronutrients to mitigate the food and nutritional security of the ever-increasing population. Antinutritional factors like phytates, raffinose (RFO’s), oxalates, tannin etc. have ill effects on human health upon consumption. Reduction of the anti-nutritional factors or preventing their accumulation offers opportunity for enhancing the intake of legumes in diet besides increasing the bioavailability of micronutrients. Besides the use of breeding methods to exploit the available genetic variability for micronutrients, modern "omic" technologies such as genomics, transcriptomics, ionomics, and metabolomics are being deployed for developing biofortified grain legumes. Molecular mechanism of Fe/Zn uptake, phytate and raffinose family oligosaccharides (RFOs) biosynthesis pathways have been elucidated. Transgenic, microRNAs and genome editing tools hold great promise for designing nutrient-dense and anti-nutrient free grain legumes. In this review we present the recent efforts towards manipulation of genes/QTLs regulating biofortification and antinutrient accumulation in legumes using genetics, genomics, microRNA and genome editing based approaches. We also discuss the success stories in legumes enrichment and recent advances in development of low antinutrient lines. We hope that these emerging tools and techniques will expedite the efforts to develop micronutrient dense legume crop varieties devoid of antinutritional factors that will serve to address the challenges like malnutrition and hidden hunger.